Design and Integration in Electro‐Optic Devices of Highly Efficient and Robust Red‐NIR Phosphorescent Nematic Hybrid Liquid Crystals Containing [Mo6I8(OCOCnF2n+1)6]2− (n = 1, 2, 3) Nanoclusters. (6th July 2015) - Prévôt, Marianne; Amela‐Cortes, Maria; Manna, Sumann K.; Lefort, Ronan; Cordier, Stéphane; Folliot, Hervé; Dupont, Laurent; Molard, Yann
Abstract : By combining [Mo6 I8 (C n F2 n +1 COO)6 ] 2‐ ( n = 1, 2, 3) nanocluster units with liquid crystalline ammonium cations, a new series of hybrid materials is developed that show a nematic liquid crystal phase, the most fluid of all LC phase, on a large range of temperatures including room temperature. The photophysical studies performed in the LC state show that these self‐assembled hybrid materials emit in the red‐NIR with absolute quantum yields up to 0.7 and show a very good photostability under continuous irradiation. They are further integrated up to 20 wt% in E7, a well‐known nematic commercial LC mixture. Mixtures are investigated in terms of homogeneity and stability to select the best suitable candidate for the design of electro‐controlled devices. Studies of optical switching, contrast, viscosity, and behavior toward an electrical stimulus demonstrate the high potential of these hybrid materials in the fields of photonic or optoelectronic. Abstract : The functionalization of highly phosphorescent [Mo6 I8 (C n F2 n +1 COO)6 ] 2− ( n = 1, 2, 3) nanocluster anionic units with appropriate ammonium cations, leads to the formation of the most fluid of all liquid crystalline phases: the nematic phase. The excellent photostability of these hybrid materials makes them suitable candidates for the design of electro‐optical devices directed toward photonic or optoelectronic applications.